Recession and adjustment : the Dominican case 1983-1985 - Rodriguez, Flavia ([s.n.] [S.l.], 1987)
Analyzes the short run impact of an economic adjustment program launched by the Dominican Republic during 1983-1985. Describes the country`s economic crisis and develops simple aggregate supply and demand model to explain the response of different economic variables to the adjustment measures. Considers the adjustment costs of the program and makes policy recommendations based on the analysis.